Altay gazeti : J K P Altay aymaqtıq komytetining organ gazeti (2020)
Online-Version (Bilddateien) der Tageszeitung des Kasachischen Autonomen Bezirks Altai in Xinjiang der Volksrepublik China in kasachischer Sprache. In dieser Zeitung werden internationale, nationale und regionale Nachrichten, Informationen und Beiträge über die Landeskunde des Bezirks Altai (Geographie, Geschichte, Politik, Tourismus, Gesellschaft, Kultur) publiziert. Diese Zeitung erscheint normalerweise mit acht Seiten. - Online version (image files) of the daily newspaper of the Kazakh Autonomous District of Altai in Xinjiang of the People's Republic of China in Kazakh language. This newspaper publishes international, national and regional news, information and articles about Altai district's regional studies (geography, history, politics, tourism, society, culture). This newspaper is usually published with eight pages.